Evolução da gestão integrada dos recursos hídricos na Bacia do Prata e perspectivas futuras - Rauber, Denise (2005)
The current dissertation identifies the integrated management evolution of the water resources in the basin of Prata, observing the aspects of the sustainable development and the water management concepts. The basin of Prata is compound of five countries, with quite differtent characteristcs, Argentina, Bolívia, Brasil, Paraguiai e Uruguai, so it was necessary the identification of the basin members countries with their characteristics and organizations, and also the iternational water treaties rescue having as focus the Basin of Prata treaty. Understanding the international relation aspects through Mercosul and its intent about the water resources. Analyze the basin member water resources policies. One evidences that the objectives of the integrated management of basins and the regional development are equivalents. Having for basic purpose the sustainable development inside of a definite region observing the relation between the resources offer and demand. This way, an integration was observed to be necessary about the future perspectives and also to be made a regional planning for the management of the water resources in the Basin of Prata. Therefore the water is a right of all, and all must be responsible for its maintenance and protectio